Pengaruh Self Efficacy terhadap Kemampuan Pemahaman Relasional Mahasiswa Matematika - Zaini, Anissa Putri; Nengsi, Heny Sri Widarna; Halki, M. Febri Ikhsan (Jurnal Pendidikan Matematika : Judika Education, 2023)
Every individual must have self-efficacy as a form of belief in themselves. Self efficacy can affect the ability of understanding, knowledge and reasoning in problem solving both daily life problems and mathematical problems. In this study we want to see the effect of self efficacy on the ability of relational understanding of mathematics students at Fatmawati Sukarno State Islamic University Bengkulu. The approach of this research is quantitative by using simple regression method and the population is mathematics students of Fatmawati Sukarno State Islamic University Bengkulu with a sample of 32 students using stratified random sampling technique. The instruments applied in this study were questionnaires and tests. Based on the results of the study, it is concluded that 43% of relational understanding ability is positively and significantly influenced by self efficacy. The higher the value of self efficacy, the higher the level of relational ability in students in working on a math problem. Keywords: Self-Efficacy, Relational Comprehension Skills